“You Are on the Right Track With the App:” Qualitative Analysis of Mobile Phone Use and User Feedback Regarding Mobile Phone Sexual Risk Assessments for HIV Prevention Research - Dietrich, Janan J.; Benadé, Gabriella L.; Mulaudzi, Mamakiri; Kagee, Ashraf; Hornschuh, Stefanie; Makhale, Lerato M.; Lemos, Maria P.; Lazarus, Erica; Andrasik, Michele P.; Horvath, Keith J. (Frontiers in Digital Health, 2021)
Background: Accurate self-report of sexual behaviour assists in identifying potential HIV exposure in HIV prevention trials. Brief mobile-phone assessments, completed daily or after sexual activity, can improve the validity and reliability of self-reported sexual behaviour and allow for remote survey completion outside of the clinic setting. We conducted a qualitative study to better understand participant mobile phone use and to explore their perspectives on how to improve an existing mobile app-based sexual risk assessment. Methods: Sexually active, HIV seronegative men (n=14) and women (n=15) aged 18-39 years were recruited through an HIV counselling and testing clinic and community outreach in Soweto, South Africa. We conducted qualitative research through four age-stratified focus group discussions (FGDs) and analysed a brief socio-demographics and mobile phone access questionnaire. All participants completed a sexual risk assessment before the FGD. Using a framework analytic approach, data were coded with Nvivo software. Results: All participants had access to mobile phones and internet, and 27 (93.1%) were able to download applications on their personal phones. Participants preferred mobile risk assessments to be offered in a choice of South African languages, using formal language (as opposed to emojis), with straight-forward wording and limited to five to ten questions. Most participants found it acceptable to complete the assessment once a week, on a weekday, while a few were willing to complete it after each sexual encounter. It was suggested that a message reminder to complete the assessment should be sent at least daily until it is completed. The majority agreed that a password-protected application with a discreet logo was ideal for privacy, ease of use and flexibility for completion in any setting. A concern with this format, however, was the potential data use requirement. Participants expressed privacy concerns with using SMS, WhatsApp and other social media for risk assessment. Most agreed on an airtime incentive between ZAR5-10 (USD 0.29-0.58) per survey. Participants encouraged researchers to provide feedback to them about their sexual risk. Conclusions: Completion of mobile phone sexual risk assessments can be optimized with minimal incentives by ensuring that questionnaires are simple, brief, infrequent and have trusted privacy measures.